Analisis Kapasitas Sungai terhadap Pengendalian Debit Banjir (Studi Kasus Sungai Kendal) - Nicko Fadhil Muhammad; Elsa Lailatut Tohiroh; Pipit Skriptianata P.P; Agus B. Siswanto (Jurnal Talenta Sipil, 2026)
Kendal Regency is located on the north coast of Java and is administratively divided into 20 districts, 265 villages, and 20 urban villages. The topography of Kendal Regency varies significantly, ranging from lowlands in the north to hilly terrain in the south. High annual sedimentation in the river channel—caused by soil erosion in the upstream areas of the Kendal watershed—can reduce the river's capacity to accommodate flood discharge. This study aims to determine the design flood discharge for the Kendal River, analyze the river's cross-sectional capacity to handle this discharge using HEC-RAS modeling, evaluate the existing capacity, and identify necessary improvements such as river normalization or levee raising. The methodology involved hydrological analysis to determine flood discharge for specific return periods and hydraulic analysis to evaluate both existing and proposed river cross-sections. The calculated design flood discharges for the Kendal River—using the Rational Method for return periods of 2, 5, 10, and 20 years—were 149.766 m³/s, 198.220 m³/s, 229.055 m³/s, and 255.484 m³/s, respectively. HEC-RAS hydraulic modeling results indicate that the existing Kendal River cross-section is incapable of accommodating the design flood discharge for these return periods; specifically, the analysis shows that the current capacity is insufficient to manage the Q20 flood event. Consequently, river normalization is recommended; a proposed normalization alternative featuring a trapezoidal cross-section—with a base width of approximately 10 meters, a top width of approximately 20 meters, and a depth of approximately 6 meters—demonstrated increased capacity in HEC-RAS simulations.